Principles of Polite Language Use for Grade XI Students at SMK Kelapa Sawit Arsya Geneeta Indonesia Pangkalan Kerinci - Siswanto, Siswanto; Afriadi, Deni; Fauzi, Rian Azmul; Adawiyah, Robiyatul (UIR Press, 2025)
Politeness in language is an important aspect of social interaction, especially in educational settings that play a role in shaping students' character. At SMK Kelapa Sawit Arsya Geneeta Indonesia, Pangkalan Kerinci, the application of politeness principles faces challenges from the influence of digital culture and social media, which tend to shift communication norms towards informality and sometimes impoliteness. This study aims to analyze the implementation of six politeness maxims according to Leech: tact, generosity, approbation, modesty, agreement, and sympathy in student interactions. A qualitative descriptive method was used, with data collected through observations, questionnaires, and documentation involving 30 purposively selected eleventh-grade students. Data analysis shows the dominance of the agreement maxim, indicating approval and harmony in interactions, followed by the tact and generosity maxims. No significant violations of politeness principles were found despite pressures from the digital environment. These findings emphasize that although communication styles change in the digital era, students’ awareness and application of politeness principles remain intact. This study highlights the importance of strengthening character education based on language ethics as an effort to shape a morally upright generation amid ongoing societal developments.